Profil Morbiditas Pasien Lansia Di Kota Bandar Lampung : Studi Cross Sectional Multicenter - Windari, Nurul Irna; Dirga, Dirga; Hidayaturahmah, Rizky; Rooswita, Putri Amelia (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: The elderly population in Indonesia has increased, including Lampung Province. Total 97.5% of elderly experience at least one chronic disease and experience multimorbid conditions whose prevalence increases with age. Only 57.7% of elderly with chronic diseases had examinations at least once every 6 months. This research is an effort to study the morbidity profile in a group of elderly patients which can be used as basic data to help planning health services.Methods: A descriptive, cross-sectional multicenter observational study with purposive sampling was conducted at three hospitals in Bandar Lampung. This study involved elderly people with chronic diseases who were undergoing outpatient treatment and met the inclusion criteria, namely age ≥ 60 years, had complete medical records, have filled out informed consent, and can communicate verbally in Bahasa. Data analysis were carried out descriptively.Result: The majority of elderly patients are pre-elderly 60.21%, male 52.25%, unemployed 77.85%, primary/junior high school education 56.06%, married 96.19%, had BPJS insurance 69.20% and low income 58.48%. The profile of morbidity were Congestive Heart Failure (CHF) 33.00%, diabetes mellitus 14.30%, hypertension 12.58%, Chronic Kidney Disease (CKD) 7.48% and stroke 5.78%. Elderly patients predominantly had 73.70% comorbidities and total 60.21% were within the normal BMI range.Conclusion : High morbidity in elderly patients requires treatment efforts to minimize it and prevent mortality. Efforts need to be made to suppress risk factors for chronic disease in the elderly.